2009
DOI: 10.1111/j.1813-6982.2009.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Persistence and Core Inflation: The Case of South Africa

Abstract: This paper analyses the persistence of inflation in South Africa since 1981. A measure of the persistence of inflation provides important information about the impact of shocks on the economy over time. This information can be extremely useful for the purpose of setting monetary policy, especially in a small, open economy like South Africa. In addition, an estimate of persistence at the disaggregate level helps in the identification of the main drivers of aggregate inflation. This information is useful in deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…In the latter, although an inflation target was set from 2000 onwards, the inflation rate appears to be non‐stationary for the whole period. This latter result is compatible with Rangasamy's (2009) result on South Africa's measurement of inflation persistence, since this author found a high degree of persistence.…”
Section: Resultssupporting
confidence: 91%
“…In the latter, although an inflation target was set from 2000 onwards, the inflation rate appears to be non‐stationary for the whole period. This latter result is compatible with Rangasamy's (2009) result on South Africa's measurement of inflation persistence, since this author found a high degree of persistence.…”
Section: Resultssupporting
confidence: 91%
“…An example of this type of core measure is the trimmed mean measure calculated in Blignaut et al . (), and the persistence and CPI weighted measure in Rangasamy (). Third, a core inflation measure should help predict future headline inflation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies such as Gilbert (2010), Cooke (2009), Leoning, Durevall, & Birru (2009), Walsh (2011), Sumlinski, Al-Eyd, Amaglobeli, & Shukurov (2012 focused food price dynamics in African countries. Rangasamy (2009) found that food inflation is highly persistent in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%